Characterization of Different Forms of Kava (Piper methysticum) Products by UPLC-MS/MS - Mamallapalli, Jessica; Kanumuri, Siva Rama Raju; Corral, Pedro; Johnston, Edward; Zhuang, Chunlin; McCurdy, Christopher R.; Mathews, Carol A.; Sharma, Abhisheak; Xing, Chengguo (Planta Medica, 2022)
There are several forms of kava (Piper methysticum) products available for human consumption, and many factors are known to influence their chemical compositions and therefore their pharmacological properties. Because of the increased popularity of kava intake, a rigorous characterization of their content diversity is prerequisite, particularly due to its known potential to cause hepatotoxicity. To understand the composition diversity of kavalactones and flavokavains in commercial kava products, we developed a UPLC-MS/MS-based analytical method for the quantification of six kavalactones (kavain, dihydrokavain, methysticin, dihydromethysticin, yangonin and desmethoxyyangonin) and two flavokavains (flavokavains A and B) and analyzed their contents in 28 different kava products in the form of capsules, tinctures, traditional aqueous suspensions and dried powders. Our results demonstrated a great variation in terms of the total and relative abundance of the analyzed kavalactones and flavokavains among the analyzed kava preparations. More importantly, the kavalactone abundance in the product label could differ up to 90% from our experimental measurements. Therefore, more rigorous and comprehensive quality control of kava products is required with respect to the content of individual kavalactones and flavokavains. Accurate content information is essential to understand the pharmacological properties and safety of different kava products.
Keywords: Kava; kavalactones; flavokavains; UPLC-MS/MS; Piper methysticum; Piperaceae